2021
DOI: 10.1136/jnnp-2021-326889
|View full text |Cite
|
Sign up to set email alerts
|

New classification of autoimmune neuropathies based on target antigens and involved domains of myelinated fibres

Abstract: Autoimmune neuropathies are named by eponyms, by descriptive terminology or because of the presence of specific antibodies and are traditionally classified, on the basis of pathology and electrophysiology, as primary demyelinating or axonal. However, autoimmune disorders targeting specific molecules of the nodal region, although not showing pathological evidence of demyelination, can exhibit all the electrophysiological changes considered characteristic of a demyelinating neuropathy and acute neuropathies with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Additionally, our protocol of teased fiber preparation and high-content confocal assessment may provide further means in the diagnostic work-up of polyneuropathies. To date, the gold-standard histopathological techniques using cross sections (40, 71, 75) do not allow detailed examination of nodes of Ranvier, although its assessment has gained importance (15). Supplemental methods to exclusively assess the node of Ranvier are sensory nerve single teased fiber analysis (40, 49, 71, 7678), electron microscopy including longitudinal sections (53, 69, 71, 74, 75, 79) and analysis of myelinated fibers in skin biopsies (71, 72, 80).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our protocol of teased fiber preparation and high-content confocal assessment may provide further means in the diagnostic work-up of polyneuropathies. To date, the gold-standard histopathological techniques using cross sections (40, 71, 75) do not allow detailed examination of nodes of Ranvier, although its assessment has gained importance (15). Supplemental methods to exclusively assess the node of Ranvier are sensory nerve single teased fiber analysis (40, 49, 71, 7678), electron microscopy including longitudinal sections (53, 69, 71, 74, 75, 79) and analysis of myelinated fibers in skin biopsies (71, 72, 80).…”
Section: Discussionmentioning
confidence: 99%
“…Different pathomechanisms lead to axonal, myelin and Schwann cell damage, resulting in severe sensorimotor deficits with disability in affected patients (12,13). In recent years, the essential role of the node of Ranvier and the severe consequences of its alterations have been studied in acquired and hereditary neuropathies, particularly in autoantibody-mediated inflammatory neuropathies (14)(15)(16)(17)(18). Yet, little is known about the ultrastructural arrangement of the node of Ranvier in polyneuropathies of other etiologies.…”
Section: Introductionmentioning
confidence: 99%
“…The term nodopathy with RCF does apply to an early phase as it takes at least two serial NCS and few weeks from onset. In the early GBS phase, CBs without abnormal temporal dispersion in the first phase can be found also in classical AIDP, which is a demyelinating paranoid-internodopathy ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, autoimmune disorders targeting specific molecules of the nodal region, although not showing pathological evidence of demyelination, may show electrophysiological changes characteristic of demyelinating neuropathy. Uncini et al propose to classify autoimmune neuropathies based on the myelin fiber domains involved (i.e., the site and molecular target of the autoimmune attack) and based on the antigen when known [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Randomized controlled trials have confirmed the efficacy of immunosuppressive/immunomodulatory treatment in patients with CIP. In these patients, electrophysiological studies find axonal lesions that do not meet electrophysiological criteria for demyelinating lesions [ 1 , 2 ]. Some authors have recently proposed that autoimmune peripheral neuropathies be subdivided into several subtypes depending on the clinical phenotype, pathophysiology and neurophysiological features—“chronic internodopathy; (CIDP)” and “nodoparanodopathy” [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%